Natural biomimetic nano-system for drug delivery in the treatment of rheumatoid arthritis: a literature review of the last 5 years - Li, Jingyuan; Li, Wei; Zhuang, Liping (Frontiers in Medicine, 2024)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease characterized primarily by synovitis, leading to the destruction of articular cartilage and bone and ultimately resulting in joint deformity, loss of function, and a significant impact on patients' quality of life. Currently, a combination of anti-rheumatic drugs, hormonal drugs, and biologics is used to mitigate disease progression. However, conventional drug therapy has limited bioavailability, and long-term use often leads to drug resistance and toxic side effects. Therefore, exploring new therapeutic approaches for RA is of great clinical importance. Nanodrug delivery systems offer promising solutions to overcome the limitations of conventional drugs. Among them, liposomes, the first nanodrug delivery system to be approved for clinical application and still widely studied, demonstrate the ability to enhance therapeutic efficacy with fewer adverse effects through passive or active targeting mechanisms. In this review, we provide a review of the research progress on the targeting mechanisms of various natural biomimetic nano-delivery systems in RA therapy. Additionally, we predict the development trends and application prospects of these systems, offering new directions for precision treatment of RA.